2019
DOI: 10.3390/cancers11070988
|View full text |Cite
|
Sign up to set email alerts
|

The Interplay between Colon Cancer Cells and Tumour-Associated Stromal Cells Impacts the Biological Clock and Enhances Malignant Phenotypes

Abstract: Cancer cells interrelate with the bordering host microenvironment that encompasses the extracellular matrix and a nontumour cellular component comprising fibroblasts and immune-competent cells. The tumour microenvironment modulates cancer onset and progression, but the molecular factors managing this interaction are not fully understood. Malignant transformation of a benign tumour is among the first crucial events in colorectal carcinogenesis. The role of tumour stroma fibroblasts is well-described in cancer, … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
26
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(30 citation statements)
references
References 48 publications
3
26
0
Order By: Relevance
“…In addition to the modelling approach, the data from our spheroid assay indicates that the 3D architecture of cells in the host may have an impact on the reduced cell proliferation observed in vivo and offer an alternative explanation for the observed phenotype ( Figure 4P). Altogether, our data highlights a profound role for tumour microenvironment in affecting cancer behaviour in terms of proliferation, apoptosis and metastatic potential, likely due to the cancer/host circadian clock interplay, as seen previously using co-culture experiments with colon cancer cells [35]. Our work highlights the different functionalities of the colon cancer circadian clock as a function of their environmental conditions (in vitro vs. in vivo), and their implications on the cancer phenotype.…”
Section: Discussionsupporting
confidence: 74%
“…In addition to the modelling approach, the data from our spheroid assay indicates that the 3D architecture of cells in the host may have an impact on the reduced cell proliferation observed in vivo and offer an alternative explanation for the observed phenotype ( Figure 4P). Altogether, our data highlights a profound role for tumour microenvironment in affecting cancer behaviour in terms of proliferation, apoptosis and metastatic potential, likely due to the cancer/host circadian clock interplay, as seen previously using co-culture experiments with colon cancer cells [35]. Our work highlights the different functionalities of the colon cancer circadian clock as a function of their environmental conditions (in vitro vs. in vivo), and their implications on the cancer phenotype.…”
Section: Discussionsupporting
confidence: 74%
“…High throughput metabolic profiling by Seahorse extracellular flux assays made it possible to observe differences between quiescent, activated, and memory immune cells [425][426][427], evaluate the effects of changes in the cellular microenvironment [428][429][430],…”
Section: Methodological Considerations: Extracellular Flux Assaymentioning
confidence: 99%
“…The idea that the tumor microenvironment can disrupt circadian oscillation is supported by a study showing that healthy skin cells adjacent to a cutaneous melanoma had significantly reduced expression of clock genes [111]. Coculture experiments showed that the cancer cells circadian phenotype, metabolism and survival are affected by surrounding cells [112]. This implies something in the surrounding environment is disrupting the clocks of healthy cells, whether it is through hypoxia, acidosis or secreted factors.…”
Section: Disruption Of Tumor Circadian Rhythms By Microenvironmental mentioning
confidence: 99%